Understanding language and literacy development: diverse learners in the classroom - Wang, Xiao-Lei (Wiley, 2014)
Understanding Language and Literacy Development: Diverse Learners in the Classroom offers effective supporting strategies to address the cultural and linguistic diversity of students in contemporary classrooms. * Discusses learners with different linguistic abilities—infancy, early childhood, middle childhood, and adolescence—by suggesting effective ways to reach them based on their strengths and needs * Emphasizes language and literacy supporting strategies in a variety of everyday classroom settings * Includes activities and questions to motivate readers to think and develop their own perspectives on language and literacy development * Considers a variety of different language acquisition experiences, including monolingual, multilingual, and language impairment * Discusses different types of literacies, including digital and hypertext * Connects language and literacy development to identity and motivation to contextualize learning styles for pre-service teachers * Supported by a companion website that includes additional resources such as PowerPoint presentations by chapter and a summary of relevant information from the Common Core K–12 English Language Arts Standards